Memories of Africa : home and abroad in the United States - Falola, Toyin (Atlantic migrations and the African diaspora., 2023)
"Memories of Africa: Home and Abroad in the United States suggests a "new lens" for viewing African diaspora studies, in this case, through the experiences of African memoirists who live in the United States. The book shows how African diaspora memoirs beautifully and grippingly depict the experiences of African migrants over time through political, social, and cultural spheres. In reading African diaspora memoirs from the transatlantic slave trade period to the present, a reader can understand the complexity of the African migrant legacy and evolution. Author Toyin Falola argues that memoirs are significant not only in their interpretation of events conveyed by the memoirists but also in demonstrating how interpersonal and human the stories told can be. Memoirs are powerful because they are emotionally captivating and because important themes and events circulate around a particular person (in this case, the memoirist). Undoubtedly, a memoir is significant because it can teach anyone about a part of the human experience, even if the "facts" are not described without bias. Through this sort of narrative, the reader cannot help but enter into the memoirist's mind and, therefore, feel more empathy for them. In doing so, the reader can "feel" what the memoirist feels and "see" what the memoirist sees as clearly as is humanly possible. In this way, the historical events and life lessons become tangible and poignantly real to the reader"--